Effects of percentage fibre with treated and untreated on sound absorption properties in rubber wood fibre composite - Abd Rahman, Muhammad Hanafi; Mohamad, Zaleha (2020)
Current developments on natural fibre as sound absorption purpose have attracted researcher’s attention since sound pollution has been a threat to peoples. Hence, in this study, a fibrous acoustic material, which is rubber wood fibre, was used to determine acoustical properties. To achieve higher sound absorption coefficient (SAC) especially at low frequency, pre-treatment of the fibre is needed where in this study alkaline treatment was implemented. Three different percentages of fibre, namely 20%, 25% and 30% for non-treated and treated fibre were used to study the acoustical characteristic. Impedance tube method (ITM) was used to determine SAC. From the result, it has been found that SAC for fibre treated with alkaline was better than untreated fibre at low frequency. Alkaline treatment of the rubber wood fibre reduced the fibre diameter. More tortuous path and higher airflow resistance occurred since more fibre needed to reach the volume density of the sample. This work confirms by increasing rubber wood fibre content in the sample would also increase the acoustic performance and this has been proved where 30% of fibre sample mostly demonstrated better SAC compared to other fibre content for untreated and treated fibre and can be considered as sound absorption application.